THE CHALLENGES FOR THE DEVELOPMENT OF CHARACTER EDUCATION IN BUILDING CIVIC RESPONSIBILITY THROUGH MULTICULTURALISM PERSPECTIVE - Trisiana, Anita (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Multiculturalism is often perceived as a political instruction and the value ofdiversity in a pluralistic social order. The two terms are in fact closely related tothe world of education in which they are not mutually exclusive. It can be said liketwo sides of a coin. Various concepts relevant to multiculturalism among othersare democracy, justice and law, cultural values and ethos, unity in equal diversity,ethnic, ethnicity, ethnic culture, religious beliefs, expressions of culture, privateand publicdomain, human rights, community cultural rights, and other relevantconcepts. Multiculturalism Education is to be a challenge for the development ofnational character education implementation as a place for the achievement ofcitizensâ competences. Civic Responsibility as part of the citizenshipcompetencies is relevant to the strengthening and development of the nationâsCharacter Education as well as the development of human resources that are readyto compete in society. Indeed the diversity of Indonesian society becomes a crutchfor human resources development in Indonesia. Thus the character education doesnot only discuss issues impacting the development of the character of the nation,but comprehensively influence and impact on the establishment of the civicresponsibility. Character education as part of efforts to build the nations characteris urgent to be applied. Character education is vital andis needed to establish aânewâ Indonesia, a country which is able to face regional and global challenges.Keywords: Character Education, Civic Responsibility, Multiculturalism